Strategi Pendidikan Berkualitas Melalui Total Quality Management Berbasis PDCA - Munifah, Inayatul; Tuala, Riyuzen Praja; Murtadho, Ali (JURNAL MANAJEMEN PENDIDIKAN, 2025)
QUALITY EDUCATION STRATEGY THROUGH TOTAL QUALITY MANAGEMENT BASED ON PDCA Abstract. This study examines the implementation of Total Quality Management (TQM) that adopts the PDCA (Plan-Do-Check-Act) cycle applied to improve the quality of education at MTs Negeri 1 Bandar Lampung. This study uses a qualitative approach with data collection through observation, semi-structured interviews, and document studies. Data analysis was carried out based on the Miles and Huberman model which includes the stages of data reduction, data presentation, and drawing conclusions. The research findings reveal that the implementation of PDCA-based TQM is effective in improving the quality of education through data-based planning strategies, the use of innovative learning methods such as Problem-Based Learning and Blended Learning, and continuous data-based evaluation. Implementation ensures that students achieve minimum competency standards in subjects based on religious moderation values supported by technological innovation and routine teacher training. This study concludes that PDCA-based TQM is relevant to building a sustainable and adaptive education system to the challenges of the digital era.